Penerapan Keterampilan Membaca Sekilas dalam Memahami Karya Ilmiah - Jasmine Malaika Ramadhani; Putri Nadiarahma; Elsa Nabila Mustofa; Mahmudah Fitriyah Z.A. (Populer: Jurnal Penelitian Mahasiswa, 2024)
The purpose of this study is to investigate the effectiveness of applying reading skills at a glance in improving understanding of scientific work. The method used in this study was library study. The data in this study were obtained from reading reference books and journal articles. The result of this study is that by applying fleeting reading skills in understanding scientific work, we can improve academic literacy, help students and researchers access information quickly, and form critical and effective individuals in managing information. A fleeting reading skill is not just a technical skill, but a learning strategy that supports the achievement of higher education goals. In extensive reading, these skills are key to achieving an overall picture and basic information of scientific texts. In addition, the application of fleeting reading skills in scientific work provides significant benefits, such as time efficiency and the ability to quickly identify key information, although deep reading remains essential for comprehensive understanding.